Poverty, battered women, and work in U.S. public policy - Brush, Lisa D. (Interpersonal violence, 2011)
Introduction -- Conventional wisdom and its discontents -- What happens when abusers follow women to work? -- Calculating the costs of taking a beating -- Welfare recipients talk back -- Conclusions